PENGEMBANGAN MEDIA MULTUNO STEP UP BERBASIS CONCRETE–PICTORIAL–ABSTRACT (CPA) UNTUK MENINGKATKAN PENALARAN MATEMATIS MATERI PERKALIAN KELAS 3 SD - Fernandin Rosa Kurnianing Tyas; Dani Kusuma (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Mathematical reasoning skills of elementary school students in multiplication learning still need improvement because instruction is often abstract and less aligned with students’ learning characteristics. Therefore, the Concrete–Pictorial–Abstract (CPA) approach was selected to help students understand multiplication concepts gradually through concrete, visual, and symbolic representations. This study aimed to develop CPA-based MULTUNO Step Up media to improve the mathematical reasoning skills of third-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model and involved 34 third-grade students of SD Negeri Baran 02. The development process consisted of needs analysis, media design, product development, implementation in classroom learning, and evaluation to refine the developed product. Data were collected through observations, interviews, tests, questionnaires, and documentation. The novelty of this study lies in the development of MULTUNO Step Up media that integrates the CPA approach into multiplication learning to support students’ mathematical reasoning. The results showed that the media was categorized as highly feasible based on expert validation by media and subject-matter experts. The effectiveness test yielded a Sig. (2-tailed) value of 0.000 < 0.05, while the N-Gain test produced an average score of 0.8535, which falls into the high category. Therefore, CPA-based MULTUNO Step Up media is effective for teaching multiplication and has the potential to serve as an innovative learning medium for enhancing elementary school students’ mathematical reasoning skills. ABSTRAK Kemampuan penalaran matematis siswa sekolah dasar pada materi perkalian masih perlu ditingkatkan karena pembelajaran sering kali bersifat abstrak dan kurang sesuai dengan karakteristik belajar siswa. Oleh karena itu, pendekatan Concrete–Pictorial–Abstract (CPA) dipilih untuk membantu siswa memahami konsep perkalian secara bertahap melalui representasi konkret, visual, dan simbolik. Penelitian ini bertujuan mengembangkan media MULTUNO Step Up berbasis CPA untuk meningkatkan penalaran matematis siswa kelas III SD. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE yang melibatkan 34 siswa kelas III SD Negeri Baran 02. Tahapan pengembangan meliputi analisis kebutuhan, perancangan media, pengembangan produk, implementasi dalam pembelajaran, dan evaluasi untuk menyempurnakan produk yang dihasilkan. Data dikumpulkan melalui observasi, wawancara, tes, angket, dan dokumentasi. Kebaruan penelitian terletak pada pengembangan media MULTUNO Step Up yang mengintegrasikan pendekatan CPA dalam pembelajaran perkalian untuk mendukung penalaran matematis siswa. Hasil penelitian menunjukkan bahwa media memperoleh kategori sangat layak berdasarkan validasi ahli media dan ahli materi. Uji efektivitas menunjukkan nilai Sig. (2-tailed) sebesar 0,000 < 0,05, sedangkan uji N-Gain memperoleh rata-rata 0,8535 dengan kategori tinggi. Dengan demikian, media MULTUNO Step Up berbasis CPA efektif digunakan dalam pembelajaran perkalian dan berpotensi menjadi alternatif media inovatif untuk mengembangkan penalaran matematis siswa sekolah dasar.